n → ∞ lim ( n ln 1 + ln 2 + ln 3 + ⋯ + ln n − ln n ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
lim n → ∞ n l n ( 1 ) + l n ( 2 ) + l n ( 3 ) + . . . + l n ( n ) − l n ( n )
which leads to
lim n → ∞ n l n ( 1 ) + l n ( 2 ) + l n ( 3 ) + . . . + l n ( n ) − n ∗ l n ( n )
Since there are n terms of the sum, and n -ln(n)s, there is exactly one -ln(n) for every part of the series, meaning
lim n → ∞ n 1 ∗ [ l n ( n 1 ) + l n ( n 2 ) + l n ( n 3 ) + . . . + l n ( n n ) ] (brackets used for clarity)
lim n → ∞ n 1 ∗ ∑ x = 1 n l n ( n x )
Can be viewed as a right Riemann sum that becomes more and more accurate to ln(x) from 0 to 1
∫ 0 1 l n ( x ) d x
which evaluates to
− 1
Riemann sums are used to define the proper Riemann integrals of bounded functions. Since ln x is not bounded on ( 0 , 1 ) , its integral is an improper Riemann integral, which is not automatically defined in terms of Riemann sums. If you are going to use integration and not Stirling's approximation, use the monotonicity of ln x . See my solution.
Since the function ln x is monotonic increasing on ( 0 , ∞ ) , we see that L n = n 1 r = 1 ∑ n ln ( n r ) ≥ r = 1 ∑ n ∫ n r − 1 n r ln x d x = ∫ 0 1 ln x d x = − 1 Also L n ≤ r = 1 ∑ n ∫ n r n r + 1 ln x d x = ∫ n 1 1 + n 1 ln x d x and hence − 1 ≤ L n ≤ [ x ln x − x ] n 1 1 + n 1 = ( 1 + n 1 ) ln ( 1 + n 1 ) − 1 − n 1 + n ln n + n 1 = ln ( 1 + n 1 ) + n ln ( n + 1 ) − 1 so it is clear that n → ∞ lim L n = − 1
Let the value of the given limit be L. ⇒ L = n → ∞ lim n ln 1 + ln 2 + ln 3 + ⋯ + ln n − ln n ⇒ L = n → ∞ lim n 1 ( ln n 1 + ln n 2 + ln n 3 ⋯ + ln n n ) ⇒ L = n → ∞ lim r = 1 ∑ n n 1 ln n r Taking n r = x , then n 1 = d x , we can convert it into a definite integral with upper limit → n n = 1 and lower limit → n 1 = 0 ⇒ L = ∫ 0 1 ln x . d x = [ x ln x − x ] 0 1 = ( − 1 ) − 0 = − 1
See the comment I made about Jeremy's proof. Since ln x is not bounded on ( 0 , 1 ) , its integral is not directly defined in terms of Riemann sums.
Used stolz cesaro theorem..
Problem Loading...
Note Loading...
Set Loading...
The limit can be written as L = n → ∞ lim n l n ( 1 × 2 × 3 × ⋯ × n ) − l n ( n n ) = n → ∞ lim n l n ( n n n ! ) Now using Stirling formula to get the limit L = n → ∞ lim n l n ( n n e n 2 π n n n ) = L 1 + L 2 = n → ∞ lim n l n ( 2 π n ) − n → ∞ lim n l n ( e n ) For the first limit we will use L'Hopital Rule And the second will equal to − 1 Finally L 1 = n → ∞ lim n l n ( 2 π n ) = n → ∞ lim 2 n 1 = 0 And L 2 = n → ∞ lim n l n ( e n ) = 1 Therefore L = 0 − 1 = − 1